QUIZIZZ PLATFORM AS THE REALIZATION OF ASYNCHRONOUS LEARNING TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Ariani Dyah Pusparani (IAIN Syekh Nurjati Cirebon, 2021)
The purpose of this research is to discover the significant difference of using Quizizz as an asynchronous learning to students in learning vocabulary mastery of Junior High School. The research was done using a quasi-experimental design, where two classes of pre-test and post-test design were applied as the research design. 32 students of VIII C and 32 students of VIII I in SMPN 1 Kayen in the academic year 2021/2022 were taken as the sample. The students were classified into two groups as experimental and control group. The acquired data was examined using a t-test.. The result of the research expressed that the t-test had a higher value than the t-table (t-value = 3.939 > t-table = 2.00, a = 0,05). Both groups' vocabulary mastery has improved, however there is a considerable difference between the two. The experimental class learning outcomes of the post-test score had an average of 88,44 while the average of control class is 78,9. Therefore, it can be concluded that the use of Quizizz platform as asynchronous learning can improve students’ vocabulary mastery. Quizizz helps students expand their vocabulary while playing games.